Affordability of Essential Medicines and Associated Factors in Public Health Facilities of Jimma Zone, Southwest Ethiopia - Eyassu Mathewos Oridanigo; Waju Beyene Salgedo; Feyera Gebissa Kebene (Hindawi Limited, 2021)
Background. Affordability is one of the key dimensions for access to essential medicines, and poor affordability impedes access to treatment in health facilities. The concept of affordability is associated with the issue of impoverishment and catastrophic expenditure. The provision of affordable and appropriate essential medicines is a vital component of a well-functioning health system. Objective. The objective of this study was to assess the perceived affordability of essential medicines and associated factors in public health facilities of the Jimma Zone, Southwest Ethiopia. Methods. A facility-based cross-sectional study design was employed. The study was conducted from March 28 to April 30, 2018, in the public health facilities of Jimma Zone, Southwest Ethiopia. Based on the WHO operational package for assessing, monitoring, and evaluating a country's pharmaceutical situations, health facilities were selected from each selected district using lower-, middle-, and higher-level criteria, making a total of 30 health facilities. For the exit interview, the total sample size was proportionally allocated for each of the selected health facilities. The data from the patient exit interview were collected using interviewer-administered structured questionnaires. The data were checked for their completeness, edited, and coded. Following this, they were entered into EpiData 3.1 and exported to SPSS version 23 for analysis. Multivariable logistic regression analysis was performed using the backward LR method to identify factors independently associated with dependent variables. Result. Six hundred and six patients participated in the study with a response rate of 97%. Among the total patients, 63.9% characterized the prescribed medicines as not affordable. The level of the health facility [AOR (95% CI) = 3.848(2.144,6.905) and p≤0.001], number of dispensed medicines [AOR (95% CI) = 0.326(0.215-0.493) and p≤0.001], occupation [AOR (95% CI) = 3.354(1.793-6.274) and p≤0.001], family income [AOR (95% CI) = 3.897(1.497-10.145) and p=0.005], place of residence [AOR (95% CI) = 2.100(1.331-3.315) and p=0.001] and number of economically dependent family members [AOR (95% CI) = 2.206(1.165-4.175) and p=0.015] were significantly associated with the perceived affordability of essential medicines. Conclusion. The average cost of dispensed medicines in the surveyed health facilities was not affordable for most of the patients. We recommend both social- and community-based health insurance schemes should be expanded to the study area.